2007
DOI: 10.1038/sj.eye.6702972
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the gap junction protein Connexin 43 in keratoconus

Abstract: Purpose The purpose of the present study was to examine whether keratoconus, which is a bilateral noninflammatory corneal ectasia with multifactorial aetiology, shows altered expression of Connexin (Cx43). Cx43 is an important gap junction protein that contributes crucially to epithelial and stromal integrity of cornea. Methods Eight keratoconic human corneal buttons were examined with immunohistochemistry and Western blotting and compared with eight normal human corneal buttons, to unravel changes in Cx43 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…These functions are important in the healthy corneal epithelium which is constantly undergoing renewal through the processes of cell division, migration and differentiation. These functional classifications are consistent with histological observations of KC epithelium, which typically appear flattened and thinned, with fewer layers and diminished architecture of the basal and wing cell layers, associated with changes in cell-cell junctions and loss of cell polarity 3 , 5 , 37 . The regulation of hydrolase activity category was also down-regulated, however the hydrolase-related DEGs identified in our study did not include the previously suggested MMPs and TIMPs 20 .…”
Section: Discussionsupporting
confidence: 88%
“…These functions are important in the healthy corneal epithelium which is constantly undergoing renewal through the processes of cell division, migration and differentiation. These functional classifications are consistent with histological observations of KC epithelium, which typically appear flattened and thinned, with fewer layers and diminished architecture of the basal and wing cell layers, associated with changes in cell-cell junctions and loss of cell polarity 3 , 5 , 37 . The regulation of hydrolase activity category was also down-regulated, however the hydrolase-related DEGs identified in our study did not include the previously suggested MMPs and TIMPs 20 .…”
Section: Discussionsupporting
confidence: 88%
“…In the cornea, the regulation of cell shedding establishes a foundation for corneal tissue engineering, enabling maintenance of cell growth (i.e. prevention of cell death), and potentially the treatment of corneal thinning diseases such as keratoconus (Gatzioufas et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…37 We have previously shown that Cx43 is expressed in the normal rabbit corneal epithelium and that its expression in this tissue is lost during wound healing. 38 Moreover, immortalized corneal epithelial cells were found to have lost the expression of Cx43 and GJIC.…”
Section: Figure 4 Effects Of Mapk Inhibitors Onmentioning
confidence: 99%